Beliefs and practices of Brazilian EFL teachers regarding pronunciation. (September 2016) - Buss, Larissa
Interest in pronunciation learning and teaching has increased significantly in the past few years. Studies and resources in the area have proliferated, but it is important to know whether they have influenced teachers of English as a foreign language (EFL) and English as a second language (ESL). The purpose of this study was to investigate the beliefs and practices of Brazilian EFL teachers. Convenience and snowball sampling were employed to recruit 60 participants, who completed an online survey on pronunciation teaching and learning. Descriptive statistics was used to analyse trends, while qualitative responses were coded for common topics. The findings suggest that the instructors had generally informed views about pronunciation and positive attitudes toward its teaching. Their teaching practices tended to be traditional: the predominant approach was to deal with word-level features, especially problematic sounds, through repetition as the need arose. Although most of the respondents claimed to be comfortable teaching pronunciation, they reported a wish for more pronunciation training, as have other instructors in prior studies (e.g. Burgess & Spencer, 2000; Foote, Holtby, & Derwing, 2011).